Re-investigation of the resource curse hypothesis: The role of political institutions and energy prices in BRIC countries. (December 2020) - Hussain, Muzzammil; Ye, ZhiWei; Usman, Muhammad; Mir, Ghulam Mustafa; Usman, Ahmad; Abbas Rizvi, Syed Kumail
Abstract: The resource curse hypothesis is widely debated in the literature with the exploration of many responsible reasons, but the papers are scarce on the role of political institutions, energy prices, and financial development in developing countries. Therefore, the present study is an effort to contribute to the existing body of knowledge by recruiting political institutions and energy prices to examine financial development with the most comprehensive (IMF's index) in BRIC (Brazil, Russia, China, and India) in a framework of resource endowment theory. By using the maximum data available from 1992 to 2016, short- & long-run relationships are estimated through cross-section augmented autoregressive distributive lag model (CS-ARDL) along with a common correlated effect mean group (CCEMG). As per the results of the above-mentioned second-generation econometric techniques, political-institutional quality is positively effecting financial development, implying better quality of institutions is strengthening financial development. Whereas, energy prices are negatively effecting financial development. Moreover, the resources are found as a blessing for BRIC economies. Overall, BRIC economies need to control the prices of the energy sector to promote financial development in the future. Findings are also vigorous for the policy implications thereto. Highlights: We re-examined the resource-curse hypothesis in BRIC countries. The role of political institutions and energy prices is studied by using IMF's FD index. Second generation econometric techniques are applied. Findings reveals the resources as blessings. Institutional quality is helping to promote financial development in BRIC economies.